Soliton-like Solutions for Some Nonlinear Evolution Equations through the Generalized Kudryashov Method (Global Journal of Science Frontier Research, 2017)
In this present article, we apply the generalized Kudryashov method for constructing ample new exact traveling wave solutions of the (2+1)-dimensional Breaking soliton (BS) equation, (2+1)-dimensional Burgers equation and (2+1)-dimensional Boussinesq equation. We attain successfully numerous new exact traveling wave solutions. This method is candid and concise, and it can be also applied to other nonlinear evolution equations in mathematical physics and engineering sciences. Moreover, some of the newly attained exact solutions are demonstrated graphically.
Keywords: generalized kudryashov method; BS equation; burgers equation; boussinesq equation; NLEEs